2018
DOI: 10.1073/pnas.1802519115
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ABCA4 in the retinal pigment epithelium and its implications for Stargardt macular degeneration

Abstract: SignificanceRecessive Stargardt macular degeneration (STGD1) and a subset of cone–rod dystrophies are caused by mutations in the Abca4 gene. The ABCA4 protein is a flippase in photoreceptor cells that helps eliminate retinaldehyde, a toxic photoproduct of vision. Here we found that ABCA4 is additionally present in the retinal pigment epithelium (RPE) of mice at approximately 1% of its abundance in the neural retina. Genetically modified mice that express ABCA4 in RPE but not in photoreceptor cells showed parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(145 citation statements)
references
References 35 publications
5
125
1
Order By: Relevance
“…Recently, it was shown that bisretinoids formation can be initiated endogenously in the RPE, independently of the photoreceptor pathway, from the free retinaldehydes released after rhodopsin proteolysis. Lenis et al showed that the absence of ABCA4 in the RPE internal membranes led to the enhanced deposition of bisretinoids . In rodents, RPE cells in the central retina contain a higher level of lipofuscin and a lower level of melanin than in the peripheral retina .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was shown that bisretinoids formation can be initiated endogenously in the RPE, independently of the photoreceptor pathway, from the free retinaldehydes released after rhodopsin proteolysis. Lenis et al showed that the absence of ABCA4 in the RPE internal membranes led to the enhanced deposition of bisretinoids . In rodents, RPE cells in the central retina contain a higher level of lipofuscin and a lower level of melanin than in the peripheral retina .…”
Section: Discussionmentioning
confidence: 99%
“…Lenis et al showed that the absence of ABCA4 in the RPE internal membranes led to the enhanced deposition of bisretinoids. 8 In rodents, RPE cells in the central retina contain a higher level of lipofuscin and a lower level of melanin than in the peripheral retina. 40,41 The RPE degeneration induced by blue light was mainly located in the central area of eyes in pigmented Abca4 −/− mice, consistent with the spatial distribution of phototoxic RPE lipofuscin and RPE melanin that is known to have antioxidative properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly significant and large (58%) foveal upregulation was only observed in pigment epithelial cells but not in rods and cones, in which ABCA4 is also expressed. Stargardt disease, caused by mutations in the ABCA4 gene, may thus originate in fovea-specific dysfunction of pigment epithelial cells (Lenis et al, 2018). Therapy for Stargardt disease should therefore focus on gene replacement or editing not only of photoreceptors but also of pigment epithelial cells.…”
Section: Functionally Intact Human Retinamentioning
confidence: 99%
“…In contrast to the current study, Mookherjee et al (2015) employed the photoreceptor-specific rhodopsin kinase promoter to drive expression of the RP2 gene, and using this specific promoter achieved a partial rescue of the cone phenotype in one of the null RP2 mouse models, but had no beneficial effect on the rod phenotype. In the context of the requirement or otherwise for transgene expression in multiple cell types, it is notable that a recent study of ABCA4-linked Stargardt disease demonstrated that, while ABCA4 is expressed in the RPE at only about 1% the level of that in photoreceptors, restricted expression of ABCA4 solely in RPE cells provided partial rescue of the photoreceptor degeneration in ABCA4 -/mice (Lenis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%